Non-destructive testing device and method for corrosion of heterogeneous material connection structure

By using information probes and electrochemical measuring instruments for online inspection in heterogeneous material connection structures, the problem of corrosion detection of heterogeneous material connection parts in the prior art requires damage to the structure, and high-precision non-destructive detection and material corrosion performance evaluation are achieved.

CN119688570APending Publication Date: 2025-03-25CRRC QINGDAO SIFANG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411824833.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The corrosion detection of existing heterogeneous material connectors mostly requires damage to the structure, which cannot achieve high-precision online detection, and it is difficult to evaluate the impact of riveting on the corrosion performance of materials.

Method used

A non-destructive corrosion measurement device for heterogeneous material connecting structures is provided, including a first information probe, a second information probe, an electrochemical measuring instrument, an ion conductor and a reference electrode. By obtaining the potential and corrosion current of the contact material online, determining the anode and cathode, and adjusting the probe area according to the actual surface area to obtain a more accurate galvanic current density.

Benefits of technology

It realizes rapid non-destructive testing of heterogeneous material connection structures, avoids structural damage, improves the accuracy of corrosion detection, and can distinguish the galvanic corrosion sensitivity level of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119688570A_ABST
    Figure CN119688570A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of corrosion monitoring of heterogeneous material connection structures. The invention provides a nondestructive testing device and method for corrosion of a heterogeneous material connection structure, and the nondestructive testing device comprises a first information probe, a second information probe, an electrochemical measuring instrument, an ion conduction device and a reference electrode, the bottom end of the first information probe is used for being connected to the surface of an A material, the contact area of the first information probe and the surface of the A material is adjustable, the bottom end of the second information probe is used for being connected to the surface of a B material, and the contact area of the second information probe and the surface of the B material is adjustable. According to the method, the area of the information probe can be modified according to the actual surface area of the contact material, so that the more accurate galvanic current density of the anode material in the galvanic pair is obtained, the galvanic corrosion sensitivity grade is distinguished, and the corrosion nondestructive measurement precision is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of corrosion monitoring of heterogeneous material connection structures, and in particular to a non-destructive measurement device and method for corrosion of heterogeneous material connection structures. Background Art

[0002] In the body structure, riveting is an important connection method in rail vehicle structure, which has the advantages of simple process, earthquake resistance, firmness and reliability. At present, the evaluation of riveting reliability mainly focuses on the mechanical properties of the riveted structure itself, but lacks analysis of the influence of this connection method on the corrosion performance of materials.

[0003] Riveted structural parts usually connect different materials (not limited to metals, such as carbon fiber, titanium alloy, aluminum alloy, weather-resistant carbon steel, etc.). When dissimilar materials are connected and contacted, due to the difference in their physical and chemical properties, galvanic corrosion risks are easily caused. If not discovered in time, in addition to affecting the appearance of the vehicle product, more importantly, it is difficult to maintain the connection strength between the original materials, reducing the safety factor. Currently, most existing corrosion detection of dissimilar material connectors requires the destruction of the structural parts, and cannot achieve high-precision online detection. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a device and method for non-destructive measurement of corrosion of heterogeneous material connection structures, which can obtain the potential and corrosion current of two contact materials in the heterogeneous material connection structure online, and at the same time determine the anode phase and the cathode phase, the information probe area can be modified according to the actual surface area of ​​the contact material, so as to obtain a more accurate galvanic current density of the anode material in the galvanic pair, distinguish its galvanic corrosion sensitivity level, and improve the accuracy of non-destructive measurement of corrosion.

[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0006] In a first aspect, the present invention provides a device for non-destructive measurement of corrosion of a heterogeneous material connection structure.

[0007] A non-destructive measuring device for corrosion of a heterogeneous material connection structure, comprising: a first information probe, a second information probe, an electrochemical measuring instrument, an ion conductor and a reference electrode;

[0008] The bottom end of the first information probe is used to connect to the surface of material A, and the contact area between the first information probe and the surface of material A is adjustable; the bottom end of the second information probe is used to connect to the surface of material B, and the contact area between the second information probe and the surface of material B is adjustable;

[0009] The inner cavity of the first information probe and the inner cavity of the second information probe are both used to contain electrolyte solution, the top of the first information probe is connected to the first end of the ion conductor, the top of the second information probe is connected to the second end of the ion conductor, and the reference electrode is arranged in the inner cavity at the middle position of the ion conductor;

[0010] The reference electrode is connected to the reference electrode connector of the electrochemical measuring instrument, the working electrode connector of the electrochemical measuring instrument is used to connect to the A material, and the counter electrode connector of the electrochemical measuring instrument is used to connect to the B material.

[0011] As a further limitation of the first aspect of the present invention, the top of the first information probe is connected to the first end of the ion conductor through a first connecting piece, and a first injection hole is formed on the first connecting piece.

[0012] As a further limitation of the first aspect of the present invention, the top of the second information probe is connected to the second end of the ion conductor via a second connecting piece, and a second injection hole is formed on the second connecting piece.

[0013] As a further limitation of the first aspect of the present invention, the first connecting member and the second connecting member are both three-way valves.

[0014] As a further limitation of the first aspect of the present invention, the heterogeneous material connection structure includes a first structural member and a second structural member that are not in direct contact and indirect contact, and the first structural member and the second structural member are both formed by connecting material A and material B, and the connection method is the same;

[0015] The bottom end of the first information probe is used to connect to the surface of material A of the first structural member, and the bottom end of the second information probe is used to connect to the surface of material B of the second structural member;

[0016] The working electrode connector of the electrochemical measuring instrument is used to connect with the material A of the first structural member, and the counter electrode connector of the electrochemical measuring instrument is used to connect with the material B of the second structural member.

[0017] As a further limitation of the first aspect of the present invention, the first information probe and the second information probe have the same structure, and both include:

[0018] A fixed frame, a movable pair, a knob screw and a top cover, wherein the movable pair is sealed and fixed at different positions of the fixed frame by the knob screw to adjust the bottom contact area, and the top cover is sealed and fixedly connected to the fixed frame and the top of the movable pair.

[0019] As a further limitation of the first aspect of the present invention, the bottom end of the first information probe is used to connect to the surface of material A through a sealing strip and sealing silicone, and the bottom end of the second information probe is used to connect to the surface of material B through a sealing strip and sealing silicone.

[0020] As a further limitation of the first aspect of the present invention, the ion conductor is a T-shaped tube for filling an electrolyte solution, and the reference electrode is arranged in a downwardly protruding inner cavity at a middle position of the T-shaped tube.

[0021] As a further limitation of the first aspect of the present invention, it further includes a computer terminal, and the computer terminal is connected to the electrochemical measuring instrument.

[0022] In a second aspect, the present invention provides a method for non-destructive measurement of corrosion of a heterogeneous material connection structure.

[0023] A method for nondestructive measurement of corrosion of a heterogeneous material connection structure, using the nondestructive measurement device for corrosion of a heterogeneous material connection structure according to the first aspect of the present invention, comprises the following steps:

[0024] Obtaining a first ratio of the surface areas of material A and material B so that a ratio of the contact area of ​​the first information probe to the contact area of ​​the first information probe is equal to the first ratio;

[0025] Clean the surface of the material to be tested, connect the first information probe to the surface of material A, and connect the second information probe to the surface of material B;

[0026] Injecting electrolyte solutions into the inner cavity of the first information probe and the inner cavity of the second information probe respectively, so that the reference electrode is inserted into the electrolyte solution, and starting the electrochemical measuring instrument after the electrode environment is stable;

[0027] Keep the A material of the first information probe and the working electrode connector of the electrochemical measuring instrument in a conductive state, set the B material of the second information probe and the counter electrode connector of the electrochemical measuring instrument to be disconnected, and test to obtain the open circuit potential E of the A material. A ;

[0028] Keep the carbon fiber of the second information probe and the counter electrode connector of the electrochemical measuring instrument in a conductive state, set the titanium alloy of the first information probe and the working electrode connector of the electrochemical measuring instrument to be disconnected, and test to obtain the open circuit potential E of the carbon fiber. B ;

[0029] The A material of the first information probe is kept in a conductive state with the working electrode connector of the electrochemical measuring instrument, and the carbon fiber of the second information probe is kept in a conductive state with the counter electrode connector of the electrochemical measuring instrument, and a galvanic experiment test is performed;

[0030] According to the open circuit potential E Aand open circuit potential E B , determine the anode material, if the open circuit potential E A and open circuit potential E B The absolute value of the difference is greater than or equal to the critical value of galvanic corrosion, which indicates that the corrosion of the anode material has intensified;

[0031] The galvanic current-time relationship diagram is obtained according to the galvanic experimental test results, the galvanic current density of the anode material is calculated, and the galvanic corrosion sensitivity level of the anode material is determined according to the galvanic current density.

[0032] The beneficial effects of the present invention are as follows:

[0033] 1. The present invention innovatively proposes a nondestructive measurement device for corrosion of heterogeneous material connection structures. Through the cooperation of a first information probe, a second information probe, an electrochemical measuring instrument, an ion conductor and a reference electrode, rapid nondestructive detection of heterogeneous material connection structures is achieved, thereby avoiding damage to the heterogeneous material connection structures during testing.

[0034] 2. The present invention innovatively proposes a non-destructive measurement device for corrosion of heterogeneous material connection structures. The two information probes each include a fixed frame, a movable pair, a knob screw and a top cover. The movable pair is sealed and fixed at different positions of the fixed frame by a knob screw to adjust the bottom contact area. The top cover (with a channel connected to the ion conductor) is sealed and fixedly connected to the top of the fixed frame and the movable pair. The area of ​​the information probe can be modified according to the actual surface area of ​​the contact material, which greatly improves the test accuracy.

[0035] 3. The top of the first information probe of the present invention is connected to the first end of the ion conductor through a first connecting piece, and a first injection hole is provided on the first connecting piece. The top of the second information probe is connected to the second end of the ion conductor through a second connecting piece, and a second injection hole is provided on the second connecting piece. The injection hole can be used to achieve re-injection after initial injection and sealing, thereby ensuring the effective implementation of electrochemical measurement.

[0036] 4. The present invention innovatively proposes a non-destructive measurement method for corrosion of heterogeneous material connection structures, which can obtain the potential and corrosion current of two contact materials in the heterogeneous material connection structure online, and at the same time determine the anode phase and the cathode phase. The information probe area can be modified according to the actual surface area of ​​the contact material, thereby obtaining a more accurate galvanic current density of the anode material in the galvanic pair, distinguishing its galvanic corrosion sensitivity level, and improving the accuracy of non-destructive corrosion measurement. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0038] Figure 1 A schematic diagram of the cross-sectional structure of the information probe provided by the present invention;

[0039] Figure 2 An overview of the non-destructive measurement device for corrosion of heterogeneous connected structural parts provided by the present invention;

[0040] Figure 3 The galvanic corrosion current diagram of the titanium alloy and carbon fiber tested provided by the present invention;

[0041] Figure 4 The galvanic corrosion current diagram of the titanium alloy and the aluminum alloy (1:1) tested provided by the present invention;

[0042] Figure 5 The galvanic corrosion current diagram of the titanium alloy and the aluminum alloy (1:9) tested by the present invention;

[0043] Figure 6 They are Figure 4 and Figure 5 Example of SEM image of aluminum alloy surface;

[0044] Among them, 1. fixed frame; 2. moving pair; 3. knob screw; 4. sealing strip; 5-1. first connecting part; 5-2. second connecting part; 6-1. first injection hole; 6-2. second injection hole; 7. ion conductor; 8. reference electrode; 9-1. first information probe; 9-2. second information probe; 10. A material; 11. B material; 12. working electrode connector; 13. reference electrode connector; 14. counter electrode connector; 15. mobile computer; 16. top cover; 17. adjustable area; 18. first structural part; 19. second structural part; 20. electrochemical measuring instrument. DETAILED DESCRIPTION

[0045] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0046] As described in the background technology, the existing corrosion detection of heterogeneous material connectors mostly requires the destruction of the structural parts, and online detection cannot be achieved. In view of this, the present implementation provides a non-destructive measurement device for corrosion of heterogeneous material connection structures, including: a first information probe 9-1, a second information probe 9-2, an electrochemical measuring instrument 20, an ion conductor 7 and a reference electrode 8;

[0047] In this implementation, preferably, the heterogeneous material connection structure includes a first structural member 18 and a second structural member 19 that are not in direct contact or indirect contact, and the first structural member 18 and the second structural member 19 are both formed by connecting the A material 10 and the B material 11 (the surfaces of the A material 10 and the B material 11 are flat), and the connection method is the same;

[0048] The bottom end of the first information probe 9-1 is used to connect to the surface of the A material 10 of the first structural member 18, and the bottom end of the second information probe 9-2 is used to connect to the surface of the B material 11 of the second structural member 19; the working electrode connector 12 of the electrochemical measuring instrument 20 is used to connect to the A material 10 of the first structural member 18, and the counter electrode connector 14 of the electrochemical measuring instrument 20 is used to connect to the B material 11 of the second structural member 19.

[0049] In this implementation, the inner cavity of the first information probe 9-1 and the inner cavity of the second information probe 9-2 are both used to contain electrolyte solutions, the top of the first information probe 9-1 (i.e., the top cover 16) is connected to the first end of the ion conductor 7, the top of the second information probe 9-2 (i.e., the top cover 16) is connected to the second end of the ion conductor 7, and the reference electrode 8 is arranged in the inner cavity at the middle position of the ion conductor 7;

[0050] The reference electrode 8 is connected to the reference electrode connector 13 of the electrochemical measuring instrument 20 , the working electrode connector 12 of the electrochemical measuring instrument 20 is used to connect to the A material 10 , and the counter electrode connector 14 of the electrochemical measuring instrument 20 is used to connect to the B material 11 .

[0051] In this implementation, a mobile computer 15 (i.e., a computer terminal) is also included, which is connected to the electrochemical measuring instrument 20 for processing related measurement data. It can be understood that the electrochemical measuring instrument 20 here can also have its own processing terminal (in this case, the mobile computer 15 is not required), which will not be repeated here.

[0052] In this implementation, preferably, the ion conductor 7 is a T-shaped tube, and the reference electrode 8 is inserted into the downward protrusion of the inner cavity at the middle position of the T-shaped tube. More specifically, the ion conductor 7 is a T-shaped PVC tube filled with saturated potassium chloride and gel electrolyte, which can only conduct ions.

[0053] In this implementation, preferably, the top of the first information probe 9-1 is connected to the first end of the ion conductor 7 through a first connector 5-1, and a first injection hole 6-1 is provided on the first connector 5-1. The top of the second information probe 9-2 is connected to the second end of the ion conductor 7 through a second connector 5-2, and a second injection hole 6-2 is provided on the second connector 5-2.

[0054] It can be understood that the first connecting member 5-1 and the second connecting member 5-2 here can both be three-way valves. Assuming that the first connecting member 5-1 is a three-way valve, the lower port of the three-way valve is connected to the through hole of the top cover 16, the middle port of the three-way valve is connected to the first end of the ion conductor 7, and the top port of the three-way valve is sealed and a first injection hole 6-1 is set; similarly, the second connecting member 5-2 can also be set in this way.

[0055] It can be understood that in some other implementations, the first connector 5-1 and the second connector 5-2 can also be T-shaped connectors. Assuming that the first connector 5-1 is a T-shaped connector (placed horizontally), the first port of the T-shaped connector is connected to the through hole of the top cover 16, the second port of the T-shaped connector is connected to the first end of the ion conductor 7, and the third port of the T-shaped connector is sealed and a first injection hole 6-1 is set; similarly, the second connector 5-2 can also be set in this way, which is not described in detail here.

[0056] like Figure 2 As shown, the first information probe 9-1 described in this implementation method has the same structure as the second information probe 9-2, both of which include: a fixed frame 1, a movable pair 2, a knob screw 3 and a top cover 16. The movable pair 2 is sealed and fixed at different positions of the fixed frame 1 by the knob screw 3 to adjust the bottom contact area. The top cover 16 is sealed and fixedly connected to the fixed frame 1 and the top of the movable pair 2.

[0057] In this implementation, the exposed area of ​​the heterogeneous material connection structure to be tested must be larger than the maximum adjustable area 17 of the information probe. Preferably, the adjustable range of the area of ​​the contact part between the information probe and the material to be tested is 2×2 cm 2 ~6×6cm 2 .

[0058] It can be understood that, preferably, the fixing frame 1 here is a right-angle fixing frame 1 formed by vertically connecting the first rectangular plate and the second rectangular plate (the first rectangular plate and the second rectangular plate here can be made in one piece), and the moving pair 2 includes a third rectangular plate and a fourth rectangular plate, and the bottom of the third rectangular plate is provided with a first card slot and a second card slot, the first card slot is used to vertically card in different positions on the upper part of the first rectangular plate, and the second card slot is used to vertically card on the upper part of the fourth rectangular plate, and the bottom of the fourth rectangular plate is provided with a third card slot, and the third card slot is used to vertically card on the upper part of the second rectangular plate. Among them, the first rectangular plate and the third rectangular plate are fixed by a knob screw 33 after being carded, the third rectangular plate and the fourth rectangular plate are fixed by a knob screw 33 after being carded, and the fourth rectangular plate and the second rectangular plate are fixed by a knob screw 33 after being carded.

[0059] After being fixed, the first rectangular plate, the second rectangular plate, the third rectangular plate and the fourth rectangular plate form a hollow rectangular inner cavity, the top of the inner cavity is fixed by a top cover 16 (with a through hole), and the bottom of the inner cavity is directly replaced by the surface of material A 10 or material B 11, and the inner cavity is used to fill the electrolyte solution.

[0060] In this implementation, the bottom end of the first information probe 9-1 and the surface of the A material 10 and the bottom end of the second information probe 9-2 and the surface of the B material 11 are fixedly connected through the sealing strip 4 and the sealing silicone. Preferably, the sealing silicone is Kraft K-704N silicone sealant, which needs to be left at room temperature for at least 4 hours after application to ensure complete curing of the silicone.

[0061] In this implementation, the first information probe 9-1 and the second information probe 9-2 are made of insulating materials such as polyvinyl chloride. Of course, other insulating materials can also be used, which will not be described here.

[0062] In the present implementation, preferably, the electrochemical measuring instrument 20 is a multi-channel galvanic corrosion tester; the reference electrode 8 is a saturated calomel electrode; and the solution storage chamber of each information probe is filled with a 3.5 wt. % NaCl solution (or other required electrolyte solution).

[0063] Based on the above-mentioned non-destructive measurement device for corrosion of a heterogeneous material connection structure, the present implementation also provides a non-destructive measurement method for corrosion of a heterogeneous material connection structure, comprising the following steps:

[0064] Step 1: Estimate the ratio of the surface areas of material A 10 and material B 11 of the heterogeneous material connection structure so that the ratio of the contact area of ​​the information probe is the same as the area ratio of material A 10 and material B 11.

[0065] For example, if the ratio of the surface areas of material A 10 and material B 11 is close to 1:1, the contact area between the first information probe 9-1 and material A 10 can be set equal to the contact area between the second information probe 9-2 and material B 11 (for example, the contact areas are both 2×2 cm 2 , after adjustment, tighten the knob screw 3 and seal it); if the area ratios are not equal, the contact area can be adjusted within the range of 1:1 to 1:9 (9:1);

[0066] Step 2: Use deionized water to clean the surface of the material to be tested to ensure that there are no other impurities; after cleaning, use the sealing strip 4 and the sealing silicone to connect the information probe to the surface of the material to be tested: the first information probe 9-1 is connected to the A material 10, and the second information probe 9-2 is connected to the B material 11; wait until the sealing silicone is solidified and there is no risk of leakage at the connection before proceeding to the next step;

[0067] Step 3: Fill the solution storage chamber with 3.5wt.% NaCl solution (or other suitable electrolyte solutions), connect one end of the T-shaped ion conductor 7 with the reference electrode 8 to the connection port of the top cover 16 of the first information probe 9-1 (through the first connector 5-1), and connect the other end to the connection port of the top cover 16 of the second information probe 9-2 (through the second connector 5-2); after the connection is completed, continue to add 3.5wt.% NaCl solution to the scale line through the electrolyte solution injection hole of the top cover 16 of the information probe;

[0068] Step 4: the working electrode connector 12 of the electrochemical measuring instrument 20 is connected to the A material 10, the counter electrode connector 14 of the electrochemical measuring instrument 20 is connected to the B material 11, and the reference electrode connector 13 is connected to the reference electrode 8 in the T-shaped ion conductor 7;

[0069] Step 5: After connecting the device, let it stand for 30 minutes until the electrode environment is stable, and turn on the electrochemical measuring instrument 20 and the mobile computer 15; before starting the measurement, keep the A material 10 of the first information probe 9-1 and the working electrode connector 12 of the electrochemical measuring instrument 20 in a conductive state, and set the B material 11 of the second information probe 9-2 and the counter electrode connector 14 of the electrochemical measuring instrument 20 to be disconnected, so that the open circuit potential E of the A material 10 can be measured. A Similarly, the B material 11 of the second information probe 9-2 is kept in a conductive state with the counter electrode connector 14 of the electrochemical measuring instrument 20, and the A material 10 of the first information probe 9-1 is set to be disconnected with the working electrode connector 12 of the electrochemical measuring instrument 20, and the open circuit potential E of the B material 11 can be tested. B ;

[0070] Step 6: Keep the material to be tested and the 20 electrode connectors of the electrochemical measuring instrument in a conductive state, and start the galvanic experiment test. The recommended time is 72 hours or longer. After the measurement is completed, the computer saves the data for subsequent analysis.

[0071] In the above technical solution, the open circuit potential E is obtained by sequentially maintaining the conduction between the A material 10 and the electrochemical measuring instrument 20 and maintaining the conduction between the B material 11 and the electrochemical measuring instrument 20. A and E B , the potential difference E between the two materials is E=|E A -E B |, the size of E can be used to preliminarily determine the tendency of galvanic corrosion when two materials come into contact. A and E B The positive and negative values ​​can be used to know the division of the positive and negative poles in the electric couple composed of A and B materials 11.

[0072] In the above technical solution, the electrochemical measurement data recorded by the mobile computer 15 is processed and then plotted using the Origin software to obtain a galvanic current-time relationship diagram (anode). The current change curve is integrated with the test time to obtain the galvanic current integral I (A·s), so that the galvanic current density I g (μA·cm -2 ), and compared with the galvanic corrosion sensitivity classification level in the standard HB5374-87 "Method for Determining Current of Different Metal Couples", the corrosion tendency of the material acting as the anode in the galvanic couple is rated.

[0073]

[0074] Where t is the measurement time (s), S is the contact area between the anode phase and the signal probe (cm 2 ).

[0075] Specifically, this implementation method conducted experiments with a surface area ratio of 1:1 between titanium alloy (material A 10) and carbon fiber (material B 11), a surface area ratio of 1:1 between titanium alloy (material A 10) and aluminum alloy (material B 11), and a surface area ratio of 1:9 between titanium alloy (material A 10) and aluminum alloy (material B 11), and the results are as follows.

[0076] (1) The surface area of ​​the titanium alloy (A material 10) and the carbon fiber (B material 11) is 1:1 (the contact area of ​​the first information probe 9-1 and the second information probe 9-2 is 2×2 cm 2 ).

[0077] After the device is connected, let it stand for 30 minutes until the electrode environment is stable, and turn on the electrochemical measuring instrument 20 and the mobile computer 15; before starting the measurement, keep the titanium alloy of the first information probe 9-1 and the working electrode connector 12 of the electrochemical measuring instrument 20 in a conductive state, and set the carbon fiber of the second information probe 9-2 and the counter electrode connector 14 of the electrochemical measuring instrument 20 to be disconnected, so that the open circuit potential E of the titanium alloy can be tested. A -40mV SCE Similarly, the carbon fiber of the second information probe 9-2 is kept in a conductive state with the counter electrode connector 14 of the electrochemical measuring instrument 20, and the titanium alloy of the first information probe 9-1 is set to a disconnected state with the working electrode connector 12 of the electrochemical measuring instrument 20, and the open circuit potential E of the carbon fiber can be tested. B 20mV SCE ;

[0078] Keep the material to be tested and the 20-electrode connector of the electrochemical measuring instrument in a conductive state, start the galvanic experiment test, the recommended time is 72 hours or longer, and after the measurement is completed, the computer saves the data for subsequent analysis.

[0079] By keeping only the titanium alloy and the electrochemical measuring instrument 20 connected and only the carbon fiber and the electrochemical measuring instrument 20 connected, the open circuit potential E A and E B , the potential difference E between the two materials is E=|E A -E B |=60mV, which is close to the critical value of potential difference for galvanic corrosion. The carbon fiber is used as cathode and the titanium alloy is used as anode, and the corrosion is aggravated.

[0080] The electrochemical measurement data recorded by the mobile computer 15 is processed and then plotted using Origin software to obtain a galvanic current-time relationship diagram (anode), such as Figure 3 As shown in the figure, the current change curve is integrated with the test time to obtain the galvanic current integral (A·s), from which the galvanic current density of the titanium alloy (<<0.01μA·cm -2 ), compared with the standard HB5374-87 "Method for Determining Galvanic Current of Different Metals", the galvanic corrosion sensitivity of titanium alloy is Class A, with no corrosion risk.

[0081] (2) The surface area of ​​the titanium alloy (A material 10) and the aluminum alloy (B material 11) is 1:1 (the contact area of ​​the first information probe 9-1 and the second information probe 9-2 is 2×2 cm 2 ).

[0082] After the device is connected, let it stand for 30 minutes until the electrode environment is stable, and turn on the electrochemical measuring instrument 20 and the mobile computer 15; before starting the measurement, keep the titanium alloy of the first information probe 9-1 and the working electrode connector 12 of the electrochemical measuring instrument 20 in a conductive state, and set the aluminum alloy of the second information probe 9-2 and the counter electrode connector 14 of the electrochemical measuring instrument 20 to be disconnected, so that the open circuit potential E of the titanium alloy can be tested. A -410mV SCE Similarly, the aluminum alloy of the second information probe 9-2 is kept in a conductive state with the counter electrode connector 14 of the electrochemical measuring instrument 20, and the titanium alloy of the first information probe 9-1 is set to a disconnected state with the working electrode connector 12 of the electrochemical measuring instrument 20, and the open circuit potential E of the aluminum alloy can be tested. B -761mV SCE ;

[0083] Keep the material to be tested and the 20-electrode connector of the electrochemical measuring instrument in a conductive state, start the galvanic experiment test, the recommended time is 72 hours or longer, and after the measurement is completed, the computer saves the data for subsequent analysis.

[0084] By keeping only the titanium alloy and the electrochemical measuring instrument 20 connected and only the carbon fiber and the electrochemical measuring instrument 20 connected, the open circuit potential E A and E B , the potential difference E between the two materials is E=|E A -E B |=351mV, which is higher than the potential difference at which galvanic corrosion occurs. The aluminum alloy acts as the anode, and the corrosion is aggravated.

[0085] The electrochemical measurement data recorded by the mobile computer 15 is processed and then plotted using Origin software to obtain a galvanic current-time relationship diagram (anode), such as Figure 4 As shown in the figure, the current change curve is integrated with the test time to obtain the galvanic current integral (A·s), from which the galvanic current density of the aluminum alloy (1.99μA·cm -2 ), compared with the standard HB5374-87 "Method for Determining Galvanic Current of Different Metals", the galvanic corrosion sensitivity of aluminum alloy is Class C, and there is a greater risk of galvanic corrosion when it is in contact with titanium alloy of equal area.

[0086] (3) The surface area of ​​the titanium alloy (A material 10) and the aluminum alloy (B material 11) is 1:9 (the contact area between the first information probe 9-1 and the titanium alloy is set to 2×2 cm 2 The contact area between the second information probe 9-2 and the aluminum alloy is set to 6×6cm 2 ).

[0087] After the device is connected, let it stand for 30 minutes until the electrode environment is stable, and turn on the electrochemical measuring instrument 20 and the mobile computer 15; before starting the measurement, keep the titanium alloy of the first information probe 9-1 and the working electrode connector 12 of the electrochemical measuring instrument 20 in a conductive state, and set the aluminum alloy of the second information probe 9-2 and the counter electrode connector 14 of the electrochemical measuring instrument 20 to be disconnected, so that the open circuit potential E of the titanium alloy can be tested. A -461mV SCE Similarly, the aluminum alloy of the second information probe 9-2 is kept in a conductive state with the counter electrode connector 14 of the electrochemical measuring instrument 20, and the titanium alloy of the first information probe 9-1 is set to a disconnected state with the working electrode connector 12 of the electrochemical measuring instrument 20, and the open circuit potential E of the aluminum alloy can be tested. B -791mV SCE ;

[0088] Keep the material to be tested and the 20-electrode connector of the electrochemical measuring instrument in a conductive state, start the galvanic experiment test, the recommended time is 72 hours or longer, and after the measurement is completed, the computer saves the data for subsequent analysis.

[0089] In this embodiment, the open circuit potential E is obtained by sequentially maintaining the conduction between the titanium alloy and the electrochemical measuring instrument 20 and maintaining the conduction between the carbon fiber and the electrochemical measuring instrument 20. A and E B , the potential difference E between the two materials is E=|E A -E B |=330mV, where aluminum alloy acts as anode and corrosion is aggravated.

[0090] In this embodiment, the electrochemical measurement data recorded by the mobile computer 15 is processed and then plotted using Origin software to obtain a galvanic current-time relationship diagram (anode), as shown in FIG. Figure 5 As shown in the figure, the current change curve is integrated with the test time to obtain the galvanic current integral (A·s), from which the galvanic current density of the aluminum alloy (0.72μA·cm -2 ), compared with the standard HB5374-87 "Method for Determining Galvanic Current of Different Metals", the galvanic corrosion sensitivity of aluminum alloy is Class B. When the area of ​​titanium alloy in contact with it is small, there is a small risk of galvanic corrosion.

[0091] In this implementation, we also provide Figure 4 and Figure 5 Example of SEM image of aluminum alloy surface, where: Figure 6 (a) in Figure 4 Example of SEM image of aluminum alloy surface. Figure 6 (b) in Figure 5 Example SEM image of aluminum alloy surface.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A non-destructive measurement device for corrosion of a heterogeneous material connection structure, wherein the heterogeneous material connection structure is formed by connecting material A and material B, and is characterized in that: include: A first information probe, a second information probe, an electrochemical measuring instrument, an ion conductor and a reference electrode; The bottom end of the first information probe is used to connect to the surface of material A and the contact area is adjustable, and the bottom end of the second information probe is used to connect to the surface of material B and the contact area is adjustable; The inner cavity of the first information probe and the inner cavity of the second information probe are both used to contain electrolyte solution, the top of the first information probe is connected to the first end of the ion conductor, the top of the second information probe is connected to the second end of the ion conductor, and the reference electrode is arranged in the inner cavity at the middle position of the ion conductor; The reference electrode is connected to the reference electrode connector of the electrochemical measuring instrument, the working electrode connector of the electrochemical measuring instrument is used to connect to the A material, and the counter electrode connector of the electrochemical measuring instrument is used to connect to the B material.

2. The non-destructive measurement device for corrosion of heterogeneous material connection structure according to claim 1, characterized in that: The top of the first information probe is connected to the first end of the ion conductor through a first connecting piece, and a first liquid injection hole is formed on the first connecting piece.

3. The non-destructive measurement device for corrosion of heterogeneous material connection structure according to claim 2, characterized in that: The top of the second information probe is connected to the second end of the ion conductor via a second connecting piece, and a second liquid injection hole is formed on the second connecting piece.

4. The non-destructive corrosion measuring device for heterogeneous material connection structure according to claim 3, characterized in that: The first connecting member and the second connecting member are both three-way valves.

5. The non-destructive measurement device for corrosion of a heterogeneous material connection structure according to any one of claims 1 to 4, characterized in that: The heterogeneous material connection structure includes a first structural member and a second structural member that are not in direct contact or indirect contact, wherein the first structural member and the second structural member are both formed by connecting material A and material B in the same connection manner; The bottom end of the first information probe is used to connect to the surface of material A of the first structural member, and the bottom end of the second information probe is used to connect to the surface of material B of the second structural member; The working electrode connector of the electrochemical measuring instrument is used to connect with the material A of the first structural member, and the counter electrode connector of the electrochemical measuring instrument is used to connect with the material B of the second structural member.

6. The non-destructive measurement device for corrosion of a heterogeneous material connection structure according to any one of claims 1 to 4, characterized in that: The first information probe and the second information probe have the same structure, both comprising: A fixed frame, a movable pair, a knob screw and a top cover, wherein the movable pair is sealed and fixed at different positions of the fixed frame by the knob screw to adjust the bottom contact area, and the top cover is sealed and fixedly connected to the fixed frame and the top of the movable pair.

7. The non-destructive measurement device for corrosion of a heterogeneous material connection structure according to any one of claims 1 to 4, characterized in that: The bottom end of the first information probe is used to be connected to the surface of material A through a sealing strip and sealing silicone, and the bottom end of the second information probe is used to be connected to the surface of material B through a sealing strip and sealing silicone.

8. The non-destructive measurement device for corrosion of a heterogeneous material connection structure according to any one of claims 1 to 4, characterized in that: The ion conductor is a T-shaped tube filled with an electrolyte solution, and the reference electrode is arranged in a downwardly protruding inner cavity at a middle position of the T-shaped tube.

9. The non-destructive measurement device for corrosion of a heterogeneous material connection structure according to any one of claims 1 to 4, characterized in that: Also included is a computer terminal, which is connected to the electrochemical measuring instrument.

10. A non-destructive method for measuring corrosion of heterogeneous material connection structures, characterized in that: Using the non-destructive measurement device for corrosion of heterogeneous material connection structure according to any one of claims 1 to 9, The process includes: Obtaining a first ratio of the surface areas of material A and material B so that a ratio of the contact area of ​​the first information probe to the contact area of ​​the first information probe is equal to the first ratio; Clean the surface of the material to be tested, connect the first information probe to the surface of material A, and connect the second information probe to the surface of material B; Injecting electrolyte solutions into the inner cavity of the first information probe and the inner cavity of the second information probe respectively, so that the reference electrode is inserted into the electrolyte solution, and starting the electrochemical measuring instrument after the electrode environment is stable; Keep the A material of the first information probe and the working electrode connector of the electrochemical measuring instrument in a conductive state, set the B material of the second information probe and the counter electrode connector of the electrochemical measuring instrument to be disconnected, and test to obtain the open circuit potential E of the A material. A ; Keep the carbon fiber of the second information probe and the counter electrode connector of the electrochemical measuring instrument in a conductive state, set the titanium alloy of the first information probe and the working electrode connector of the electrochemical measuring instrument to be disconnected, and test to obtain the open circuit potential E of the carbon fiber. B ; The A material of the first information probe is kept in a conductive state with the working electrode connector of the electrochemical measuring instrument, and the carbon fiber of the second information probe is kept in a conductive state with the counter electrode connector of the electrochemical measuring instrument, and a galvanic experiment test is performed; According to the open circuit potential E A and open circuit potential E B , determine the anode material, if the open circuit potential E A and open circuit potential E B The absolute value of the difference is greater than or equal to the critical value of galvanic corrosion, which indicates that the corrosion of the anode material has intensified; The galvanic current-time relationship diagram is obtained according to the galvanic experimental test results, the galvanic current density of the anode material is calculated, and the galvanic corrosion sensitivity level of the anode material is determined according to the galvanic current density.